PREDIKSI JUMLAH PENUMPANG PESAWAT PADA MASA COVID-19 DENGAN METODE EXPONENTIAL SMOOTHING - Darvi Mailisa Putri; Fitri Rahmah Ul Hasanah; Lilis Harianti Hasibuan; Miftahul Jannah (Math Educa Journal, 2022)
Forecasting is a study that is still interesting today. With the forecasting method, a person can make predictions about something based on previously available data. In this study, will be carried out on the prediction of the number of airplane passengers on domestic during the COVID-19 period. The data taken is data on domestic airplane passengers at Minangkabau International Airport Padang city. Data by month for the period 2016 to 2020. The method that will be applied to the data is the exponential smoothing type forecasting method, especially the Single Exponential Smoothing (SES) and Double Exponential Smoothing (DES) methods. The results of the study concluded that if analyzed from the MAPE value, the DES method was better with a MAPE value of 77. However, if analyzed from the MAD and MSD values, the SES method was better with a value of 32609 and 2044501652, respectively. Furthermore, analyzing the prediction results of the two methods, it was obtained that for the first four months the DES method showed better results than the SES method. But two months later the SES method was much better.